Absorption phenomena in organic thin films for solar cell applications investigated by photothermal deflection spectroscopy - Goris, L.; Haenen, K.; Nesládek, M.; Wagner, P.; Vanderzande, D.; De Schepper, L.; D’haen, J.; Lutsen, L.; Manca, J. V. (Journal of materials science, 2005)
A high sensitive approach is presented to detect in particular the low level absorption features in pure and blended organic semiconductor films, revealing a.o. defect induced sub gap absorption and new interactions between the materials. Because sub bandgap absorption features are typically characterized by very low absorption coefficients, it is not possible to resolve them using common transmission and reflection measurements. Therefore the very sensitive and ground state spectroscopic technique of Photothermal Deflection Spectroscopy (PDS) has been developed, and introduced to characterize thin films of MDMO-PPV and PCBM, as well as films of MDMO-PPV containing an increasing amount of PCBM ranging from 5 to 90% weight fraction. The measured spectra of MDMO-PPV are interpreted in terms of defect induced absorption phenomena. The spectral position of the observed transitions in PCBM have been determined and verified. The PDS-study on MDMO-PPV/PCBM blended films revealed for the first time interaction between the two materials in the ground state. To get more insight in the interaction mechanism between the constituting materials a systematic Transmission Electron Microscopy (TEM) study has been carried out to reveal the morphology of the films. The obtained TEM-results on nanomorphology of the blended films show clear correlations with the PDS-results.